The Efficacy and Safety of Combined Adductor Canal Block with Periarticular Anesthetic Injection Following Primary Total Knee Arthroplasty: A Meta-Analysis - Xiaowen Zhu; Feng Wang; Weiqi Ling; Xiaoyu Dai (Journal of Investigative Surgery, 2020)
Objective: Recently, there has been an increasing interest in combined adductor canal block (ACB) with periarticular anesthetic injection (PAI) as a technique to control postoperative pain in total knee arthroplasty (TKA). This study evaluated the analgesic efficacy and safety of the combined therapy for early postoperative pain treatment after TKA. Methods: From the inception to July 2018, two independent investigators used the following electronic databases to search existing literature: PubMed, Embase, Medline, and Web of Science. The primary outcome was pain scores, while secondary outcome measures included opioid consumption, distance walked, length of stay (LOS), and opioid-related adverse effects. Results: A total of 10 studies were included. In the outcomes of ACB + PAI versus PAI, ACB + PAI was associated with statistically significant lower pain scores on POD 0-1 (whether at rest or during movement), lower opioid consumption on POD 0-1, more distance walked on POD 1. In the outcomes of ACB + PAI versus ACB, ACB + PAI was associated with statistically significant lower pain scores on POD 0 and 1 (whether at rest or during movement), lower opioid consumption on POD 1, more distance walked on POD 1. No significant benefits of combined therapy in pain scores, opioid consumption, and distance walked were observed on POD 2. Similarly, there were no significant differences between groups in opioid-related adverse effects, and LOS. Conclusions: There is evidence that combined therapy is more effective than single therapy within 48 h following primary TKA. Applying combined therapy appears to be an effective and safe method for pain control.